SOSIOLOGI SASTRA ALAN SWINGEWOOD SEBUAH TEORI - Tri Wahyudi (POETIKA, 2013)
AbstractThis writing is a reading of the book The Sociology of Literature, written by Alan Swingewood and a briefhistory of influenced ideas. The view that literature is a sociocultural document formulated by Swingewood into anunderstood and detailed framework.Keywords: Swingewood, literature, sociology of literature.